Air-source heat pump heating based water vapor compression for localized steam sterilization applications during the COVID-19 pandemic. (July 2021) - Yan, Hongzhi; Hu, Bin; Wang, Ruzhu
Abstract: Sterilization is of great importance to prevent the spread and resurgence of the COVID-19, yet sterilization methods are all energy intensive in general. Steam sterilization is easily maintained and can be applied in various scenarios with less residual pollution. However, the current steam generator (so called boiler) has brought many energy and environmental concerns. With the investigation on steam sterilization's features, this study proposed a clean and flexible steam generation system with the air source heat pump and water vapor compressor, and the system can be further simplified through the combination with district heating pipeline. The critical design parameters and simulated performance of the system are evaluated and optimized through a MATLAB simulation, and a prototype was built with experimental performance assessing. The results show the system has an average boiler efficiency of over 170% when the ambient temperature varies from 5 °C to 35 °C and the temperature of outlet steam is above 110 °C, and has the best economic performance when the operating period is above 3 years. Furthermore, the air-source heat pump boiler system is proved to effectively respond to the surging sterilization demands during the peaks of the COVID-19 pandemic and is well consistent with the UN Sustainable Development Goals. Highlights: The steam sterilization's features and potential for various scenarios are studied. A sustainable steam generation system for steam sterilization is proposed and verified. The system absorbed free ambient heat with an average boiler efficiency over 170%. The water vapor compressor can further combine with district heating for steam generation. The system has the best economic performance when the operating period is above 3 years.